STUDENTS' LANGUAGE ATTITUDE TOWARDS ENGLISH PASCA DIGITALIZATION LEARNING - Masniati Murni Ritonga; Roni Juliansyah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
Attitude and awareness are essential factors in learning foreign language because they are reflected to the students feeling towards it. English is placed as foreign language in Indonesia play a very important role troughout human’s life academically on non-academically. It is due to English was functioned as the main ctool of communication in the world,especially in Technology era nowdays. All technology was designed in English to operate it. The phenomena happened recently was that the development of technology and the shifting process of learning spontanously onto digital,force students to be accustomed to operate digital media in learning without any well-preparation and training. Unrealizedly, students should communicate via digital media which English got alredy settled in it. Spontanously they were accustomed to interract with English words in their gadget, on the other hands, they learned autodidactly. This study amied to investigate how the students’ language attitude towards English learning pasca digitalization era. The study was designed by using qualitative with simple quantitative data survey and applying closed questionnaire that administered to respondents (all Business Administration students grade II academic Year 2021-2022). The sample was taken at all because the population was 56 students, then all of them will be the sample of the research. Furthermore, the Questionnaire will be analysed quantitatively based on the theory proposed by Miles, Huberman and Saldana such as data displaying, classifying, analyzing, comparing and concluding. Based on the study, it was found that the students shew positive attitude toward Learning English pasca digitalization learning. There were 47 students who are intereseted in learnng English and there were 8 students who felt bored in doing the English learning. Meanwhile the researher found something unique in this study, eventhough the students are interested in it, the students got 20% decressing score than before applying digital media for learning, the researchers found that there was another thing affected their score and English achivement, such as the teahers’ teaching methodology.